The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1678-4324-2021200262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoxetine Hydrochloride on Routine Metabolism of Lambari (Deuterodon iguape, Eigenmann, 1907) and Phantom Shrimp (Palaemon pandaliformis, Stimpson, 1871)

Abstract: Fluoxetine is an emerging pollutant that acts as a selective serotonin reuptake inhibitor (SSRI) and being a hydrolytic molecule that is photolytically stable and accumulaties in biological tissues, its disposal in the aquatic environment can interfere with the physiology of fish and shrimp. Thus, the objective of this study was to analyze the effects of fluoxetine on routine metabolism (metabolic rate, specific ammonia excretion and O:N ratio) of Deuterodon iguape and Palaemon pandaliformis. For this, five gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…The LC 50 value reported for fluoxetine concerning Pseudokirchneriella subcapitata (microalgae) was 24 μg/L (Brooks et al, 2003). A recent study by Rezende et al (2021) showed LC 50 values of fluoxetine after 24, 48, 72 and 96 h of 40, 36, 28 and 26 μg/L, respectively, for Palaemon pandaliformis (phantom shrimp). This shows that other organisms are clearly more sensitive to fluoxetine than D. magna.…”
Section: Lethal Effectmentioning
confidence: 97%
“…The LC 50 value reported for fluoxetine concerning Pseudokirchneriella subcapitata (microalgae) was 24 μg/L (Brooks et al, 2003). A recent study by Rezende et al (2021) showed LC 50 values of fluoxetine after 24, 48, 72 and 96 h of 40, 36, 28 and 26 μg/L, respectively, for Palaemon pandaliformis (phantom shrimp). This shows that other organisms are clearly more sensitive to fluoxetine than D. magna.…”
Section: Lethal Effectmentioning
confidence: 97%